HUBUNGAN ANTARA KELELAHAN KERJA DAN BEBAN KERJA MENTAL DENGAN STRES KERJA PETUGAS PEMADAM KEBAKARAN DAN PENYELAMATAN KABUPATEN BOGOR TAHUN 2020 - Nicky Nida'ul Husna (2021)
Work stress is caused by prolonged physical fatigue, physical workload, mental workload, and work environment. Over the past 4 years, Bogor District firefighters and rescue workers have handled the increasing incidence of fire and rescue. The number of members and the population who do not match the level of danger that varies make officers at risk of experiencing work stress. This study aims to determine the relationship between work fatigue and mental workload with work stress of firefighters in Bogor Regency. The research method used was cross-sectional analytic with a sample size of 165 officers. The technique used for sampling was purposive sampling and using the Chi-square test. The results of the research on the relationship between work fatigue and work stress obtained Pvalue 0.000 ≤ 0.05, while the relationship between mental workload and work stress was obtained Pvalue 0.034 ≤ 0.05. It can be concluded that there is a relationship between work fatigue and mental workload with work stress of firefighters and rescue Bogor Regency. It is better if the Bogor District Fire Service should increase the number of firefighters and rescue workers and carry out elimination and socialization related to the factors that cause work fatigue and mental workload so as not to cause stress to officers. Keywords: Job Stress, Work Fatigue, Mental Workload.